1982
DOI: 10.3168/jds.s0022-0302(82)82177-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Acid Inhibition of Salmonella Typhimurium in Yogurt

Abstract: We determined how lactic acid inhibits growth of Salmonella typhimurium in yogurt. This inhibition was demonstrated by microscopic examination not to be due to bacteriolysis. Neither growth nor metabolic activity could be initiated after cells were washed in phosphate buffer and exposed to 1.5% lactic acid for 1 h at 37 degrees C, indicating that lactic acid inhibition is irreversible. The growth rate of S. typhimurium at 37 degrees C, was computed at various combinations of pH and lactic acid concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…For instance, aa-PGs enhance resistance of P. aeruginosa and E. faecium to lactic acid, 35,59 a toxic osmolyte known to diffuse passively through the cytoplasmic membrane of bacteria. 97 …”
Section: Regulation Of Pg Aminoacylationmentioning
confidence: 99%
“…For instance, aa-PGs enhance resistance of P. aeruginosa and E. faecium to lactic acid, 35,59 a toxic osmolyte known to diffuse passively through the cytoplasmic membrane of bacteria. 97 …”
Section: Regulation Of Pg Aminoacylationmentioning
confidence: 99%
“…Inactivation of pathogenic bacteria in fermented milk products, including yogurt, was found by many authors (Rubin and Vaughan 1979, Rubin et al 1982, Alm 1983, Kotz et al 1990, Issa and Ryser 2000, Á lvarez-Ordóñ ez et al 2013, Cirone et al 2013. The main mechanism of bactericidal effect of yogurt on Salmonella and other pathogens seems to be the decline in pH due to lactose fermentation and the production of organic acids, mainly lactic acid, by Lactobacillus delbrueckii ssp.…”
Section: Discussionmentioning
confidence: 99%
“…bulgaricus and Streptococcus salivarius ssp. thermophilus added to the milk in starter culture before fermentation (Rubin et al 1982, Lefoka 2009, Á lvarez-Ordóñ ez et al 2013. Some authors suggest that antimicrobial activity of the yogurt is not exclusively due to the accumulation of lactic acid and may be the effect of lactic acid and other compounds such as hydrogen peroxide, carbon dioxide, acetaldehyde, polysaccharide, bacteriocins (Minj and Behera 2011).…”
Section: Discussionmentioning
confidence: 99%
“…An inactivation of pathogenic bacteria in fermented dairy products, including yogurt, has been observed in many studies (Rubin and Vaughan 1979, Rubin et al 1982, Alm 1983, Kotz et al 1990, Issa and Ryser 2000, Hlvarez-Ordóñ ez et al 2013, Cirone et al 2013. The main mechanism of bactericidal effect of yogurt on foodborne pathogens seems to be the decline in pH due to lactose fermentation by Lactobacillus delbrueckii ssp.…”
Section: Discussionmentioning
confidence: 99%
“…bulgaricus and Streptococcus salivarius ssp. thermophilus added to milk as a starter culture, as well as the production of organic acids, mainly lactic acid (Rubin et al 1982, Lefoka 2009, Hlvarez-Ordóñ ez et al 2013. Kowalik et al (2013) observed growth of L. monocytogenes in all samples of cottage cheese stored at temperature 3, 6, 9, 12 and 15 o C. They found that lag phase and growth rate of Listeria were affected not only by storage temperature but also by lactic acid concentration and pH of product ranged from 5.2 do 5.8.…”
Section: Discussionmentioning
confidence: 99%